Persepsi Konsumen terhadap Brand Reputasi Kentucky Fried Chicken (KFC) dalam Gerakan Boikot - Kanigara Tarisananda Paramesthi; Leonita Kusumawardhani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
In globalized businesses, multinational companies often face complex market dynamics involving political aspects, social and economic issues. One event that has galvanized the world is the boycott of brands. Brand boycotts are a phenomenon that can have a strong influence on company performance. The phenomenon, namely the boycott of Kentucky Fried Chicken (KFC). The boycott arose in response to KFC's alleged support for the Israeli army in the Israeli and Palestinian conflicts in the Middle East. This research intends to examine how consumers perceive KFC's brand reputation in the boycott movement. This research uses descriptive qualitative methods and data collection techniques through interviews. The results of this study are that some consumers are active in the boycott because of morals and solidarity with Palestine. The boycott affects purchase frequency, but KFC's taste quality and price are still the main factors that attract consumers. Here social media has a vital role to disseminate information and mobilize support for the boycott, so the need for information verification and in-depth consideration in boycott decisions is emphasized.